Peran Perawatan Kulit (Skincare) Yang Dapat Merawat Atau Merusak Skin Barrier - Adira Rahmawaty (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2020)
Skincare is something that is highly valued in the present. Not only women but skincare is now beginning to spread to men. Having a bright, white, acne-free skin and free from excess oil is a dream for all people. Before skincare, makeup was the first popular because of the obvious results that were clearly seen in a short time. But the world of makeup that always provides improvement for its users by covering or polishing certain parts of a person's body is now slowly starting to be abandoned and replaced with skincare. This is because so many studies and opinions have emerged that skincare is healthier and the results obtained last longer in the longer term than makeup. The large variety of skincare products that have arisen has caused controversy and consumptive behavior. It also can not be separated from the impact that is felt after the use of skincare for a long time. This article was created to discuss the impact arising from the use of skincare on the skin barrier or the outer layer of skin that protects the skin naturally from a variety of external factors that can damage the skin.